Spatial Market Integration of Garlic in Indonesia - Indah Kartika Sandra; Anna Fariyanti; Nia Kurniawati Hidayat (Budapest International Research and Critics University, 2023)
Garlic is one of the important horticultural commodities for Indonesian people. In 2020, Indonesia experienced a garlic deficit of 362.42 thousand tonnes. Indonesia's dependence on the international market causes garlic prices to tend to fluctuate. Integrated market information can help the government implement policies to reduce price fluctuations. The purpose of this study is to examine the development of garlic production, consumption, prices, and to analyze the spatial market integration of garlic in Indonesia. The data used is monthly time series data on garlic prices at the consumer level in 33 provinces for the period January 2014-December 2020. The analytical method used is Vector Error Correction Model (VECM). The results of the study show that there is a large gap between consumption and production of garlic, and the price of garlic fluctuates greatly. There has been a comprehensive long-term integration of the garlic market in Indonesia. This is indicated by the cointegration of all consumer market pairs. The consumer markets of Bali, Central Java, and East Java are price leaders. There are 212 pairs of integrated garlic consumer markets in the short term. This shows that the garlic market in Indonesia is more integrated in the long term.